2019
DOI: 10.1111/acps.13023
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of suicide rates among people discharged from non‐psychiatric settings after presentation with suicidal thoughts or behaviours

Abstract: analysis of suicide rates among people discharged from non-psychiatric settings after presentation with suicidal thoughts or behaviours.Objective: To quantify the suicide rate among people discharged from nonpsychiatric settings after presentations with suicidal thoughts or behaviours. Method: Meta-analysis of studies reporting suicide deaths among people with suicidal thoughts or behaviours after discharge from emergency departments or the medical or surgical wards of general hospitals. Results: A total of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 124 publications
0
24
0
1
Order By: Relevance
“…Although the people who provide the gate keeper role have a significant opportunity to recognize mental health symptoms and suicidal ideas early, a review their training showed that it is not standardized globally, especially as some gatekeeper training is delivered face to face and some by e‐learning. This makes it difficult to draw conclusions about the ingredients of the intervention that make the gatekeeper role effective in preventing suicide (Yonemoto, Kawashima, Endo, & Yamada, ).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Although the people who provide the gate keeper role have a significant opportunity to recognize mental health symptoms and suicidal ideas early, a review their training showed that it is not standardized globally, especially as some gatekeeper training is delivered face to face and some by e‐learning. This makes it difficult to draw conclusions about the ingredients of the intervention that make the gatekeeper role effective in preventing suicide (Yonemoto, Kawashima, Endo, & Yamada, ).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…▪ Suizidversuche und parasuizidale Handlungen in der Vorgeschichte [5,7] erhöhen das Risiko eines Suizids, ebenso wie ▪ Suizide in der persönlichen Umgebung, Suizide in der Familiengeschichte oder in Medienberichten [5,8]. ▪ Ein erhöhtes Risiko für einen Suizid besteht im ersten Monat, im ersten Jahr, etwas geringer sogar darüber hinaus nach Entlassung aus einer psychiatrischen Klinik oder einer nicht psychiatrischen Klinik bei dort aufgetretenen Suizidgedanken [9,10]. ▪ Belastende "life events" oder schwierige Lebenssituationen (durch Arbeitslosigkeit oder fehlende Bindungen), chronische und lebensverändernde Erkrankungen sowie schwere Schmerzen bergen das Risiko von Suizidgedanken oder suizidalen Handlungen [5,6] ebenso wie ▪ die Erfahrung mit psychotischen Episoden [11].…”
Section: Risikofaktoren Kennenunclassified
“…The increase in risk following healthcare contact is also seen among patients discharged from non-psychiatric settings, including emergency departments (EDs), as well. 9 The identification of suicide risk at healthcare facilities is a major priority in suicide prevention efforts. However, in recent years two distinct approaches have emerged regarding how best to do this.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the acute time period following discharge from a healthcare facility is often characterized by elevated risk for suicide attempt and death. 911 Chung et al 10 showed that across 100 studies, the rate of suicide during the first 3 months after discharge from a psychiatric facility was approximately 100 times higher than the global suicide rate. The increase in risk following healthcare contact is also seen among patients discharged from non-psychiatric settings, including emergency departments (EDs), as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation